The Adaptation of The Society in Coping with Tidal Flood in Kemijen Village Semarang City - Wiratuningsih, Dina; Setyowati, Dewi Liesnoor; Suhandini, Purwadi (Universitas Negeri Semarang, 2018)
Tidal flood is a natural phenomenon that often occurs in coastal areas and will be even greater with the increase in sea level due to global warming. Kemijen Village is located in Semarang Timur Sub-District, Semarang City, has a high population density and high slum area. This adds vulnerability to tidal flood, so it is necessary to adapt with tidal flood to reduce the impact. Adaptation is done so that the tidal flood that occurs does not have a more severe impact on the people living in the area. The purpose of this research is to analyze the adaptation of the society in coping with tidal flood in Kemijen Village. This research used a qualitative approach with in-depth research. The results of the research show that the adaptation made by the society to tidal flood is adaptation to the place of residence, adaptation to public facilities and social facilities, and social adaptation. Based on the theory of the level adaptation by Wohlwill it has been known that the adaptation of the society to the place of residence has not reached optimal levels. This research has the aim can be used as input for the development of science in this case related to adaptation in overcoming tidal floods.